Pigmentation Affects Elastic Fiber Patterning and Biomechanical Behavior of the Murine Aortic Valve - Nasim, Sana; Pandey, Popular; Kanashiro-Takeuchi, Rosemeire M.; He, Jin; Hutcheson, Joshua D.; Kos, Lidia (Frontiers in Cardiovascular Medicine, 2021)
The aortic valve (AoV) maintains unidirectional blood distribution from the left ventricle of the heart to the aorta for systemic circulation. The AoV leaflets rely on a precise extracellular matrix microarchitecture of collagen, elastin, and proteoglycans for appropriate biomechanical performance. We have previously demonstrated a relationship between the presence of pigment in the mouse AoV with elastic fiber patterning using multiphoton imaging. Here, we extended those findings using wholemount confocal microscopy revealing that elastic fibers were diminished in the AoV of hypopigmented mice (KitWv and albino) and were disorganized in the AoV of K5-Edn3 transgenic hyperpigmented mice when compared to wild type C57BL/6J mice. We further used atomic force microscopy to measure stiffness differences in the wholemount AoV leaflets of mice with different levels of pigmentation. We show that AoV leaflets of K5-Edn3 had overall higher stiffness (4.42 ± 0.35 kPa) when compared to those from KitWv (2.22 ± 0.21 kPa), albino (2.45 ± 0.16 kPa), and C57BL/6J (3.0 ± 0.16 kPa) mice. Despite the striking elastic fiber phenotype and noted stiffness differences, adult mutant mice were found to have no overt cardiac differences as measured by echocardiography. Our results indicate that pigmentation, but not melanocytes, is required for proper elastic fiber organization in the mouse AoV and dictates its biomechanical properties.